RELIGION AND LANGUAGE AS BASE IDENTIFICATION IN ERA GLOBALIZATION - Русул, О. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
In publications are considered such bases identification as religion and language from position of their determination as problem-solving realization in process universal trend globalization.